2001
DOI: 10.1097/00019606-200103000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Physical State of HPV16 and Chromosomal Mapping of the Integrated Form in Cervical Carcinomas

Abstract: Using a procedure based on restriction enzyme cleavage, self-ligation, and inverse polymerase chain reaction (rliPCR), the authors investigated 18 cervical intraepithelial neoplasia III (CIN III) cases and 37 invasive squamous carcinomas for integration of human papillomavirus type 16 (HPV16). All eighteen CIN III cases (severe dysplasia or high-grade squamous intraepithelial lesion) were found to harbor episomal HPV, but one of the samples contained mixed episomal and integrated forms. Seventeen of 37 invasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
110
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 26 publications
9
110
0
3
Order By: Relevance
“…Given our evidence that episome loss and selection of integrated HPV16 occurs very rapidly in vitro, it will be difficult to detect similar events occurring in vivo. Nevertheless, our data are supported by the observation that most cervical carcinomas containing integrated HRHPV have little or no detectable episomal DNA (3,(27)(28)(29)(30)(31). Although some carcinomas do contain both episomal and integrated virus, in situ analysis has shown that regions containing only integrated HRHPV exist adjacent to regions containing apparently only episomes (32).…”
Section: Discussionsupporting
confidence: 79%
“…Given our evidence that episome loss and selection of integrated HPV16 occurs very rapidly in vitro, it will be difficult to detect similar events occurring in vivo. Nevertheless, our data are supported by the observation that most cervical carcinomas containing integrated HRHPV have little or no detectable episomal DNA (3,(27)(28)(29)(30)(31). Although some carcinomas do contain both episomal and integrated virus, in situ analysis has shown that regions containing only integrated HRHPV exist adjacent to regions containing apparently only episomes (32).…”
Section: Discussionsupporting
confidence: 79%
“…Analysis of HPV genomes in human cancers have also demonstrated that replication by HPV E1 and E2 can result in rearranged HPV genomes. Viral genomes with deletions, insertions, or rearrangements (20,21,22,23,24) or parts of the viral genome integrated into the cellular genome (23,24) are commonly found and this is indicative of the instability of viral replication. A study using tonsillar cancer biopsies recently demonstrated that in three from eleven HPV16 episomal DNA positive samples there were episomal viral genomes with deletions, and two of these were coexistent with full-length episomal HPV DNA (24).…”
Section: Fidelity Of Hpv16 E1/e2-mediated Dna Replication 52228 Discumentioning
confidence: 99%
“…It is known that HPV E1/E2-mediated replication initiation can also occur more than once per cell cycle (19), however the fidelity of E1/E2-mediated replication is unknown. In many HPV lesions there are episomal genomes that either contain multiple insertions/deletions (20) or single deletions (21,22,23,24). The mechanisms responsible for these rearrangements could also lead to chromosomal integration of viral sequences resulting in progression to cancer.…”
mentioning
confidence: 99%
“…Activation of FGFR3 (Cappellen et al, 1999;Rosty et al, 2005a), KRAS (Crook et al, 1988;Jiko et al, 1994), HRAS (Riou et al, 1988), MYB (Nurnberg et al, 1995) and MYC (Riou et al, 1987;Zhang et al, 2002) has been reported in invasive carcinoma of the cervix. The integration of viral DNA into the host genome is seen in a minority of cervical intraepithelial neoplasia compared to a majority of invasive cancers (Cullen et al, 1991;Klaes et al, 1999;Kalantari et al, 2001) and corresponds thus to a crucial step in oncogenesis. Viral genome disruption and integration lead to the deregulated expression (Schwarz et al, 1985) and increased stability (Jeon and Lambert, 1995) of the RNA messengers derived from viral oncogenes that act in the tumor process.…”
Section: Introductionmentioning
confidence: 99%